Therapeutic value of homeoprotein signaling pathways - Di Nardo, Ariel A.; Prochiantz, Alain (Frontiers in Neuroscience, 2024)
Cell signaling based on homeoprotein transfer is a pathway with developmental and physiological functions. For a few transcription factors of this family, primarily ENGRAILED1, ENGRAILED2 and OTX2, their physiological functions have led to therapeutic strategies in animal models of human diseases, including Parkinson disease, amyotrophic lateral sclerosis, amblyopia and anxiety-related disorders. In mesencephalic dopaminergic neurons which degenerate in Parkinson disease, ENGRAILED1/2 have cell autonomous activities, but their transducing properties enables their use as therapeutic proteins. In contrast, in spinal alpha-motoneurons, which are lost in amyotrophic lateral sclerosis, ENGRAILED1 is supplied by V1 interneurons. Thus, its use as a therapeutic protein to protect alpha-motoneurons against degeneration mimics its normal non-cell autonomous neurotrophic activity. OTX2, synthesized and secreted by the choroid plexus, is transferred to parvalbumin interneurons and exerts regulatory functions controlling cerebral cortex plasticity. Understanding the latter OTX2 function has led to strategies for manipulating visual acuity and anxiety-like behavior in adult mice. In this review, we describe these cases and what is known about the involved molecular mechanisms. Because the transduction sequences are conserved in most of the few hundred homeoproteins, we argue how this family of molecules constitutes an important reservoir of physiological knowledge, with potential consequences in the search for new therapeutic strategies.